Solid state synthesis of Bi0.4Sr0.6FeO3 powder for SOFC applications (2017)
We report on the synthesis of Bi0.4Sr0.6FeO3 powder with cubic structure by solid state reaction (mechanical milling and calcination) from Bi2O3, SrCO3 and Fe2O3 stoichiometric ratios. Milled powder mixtures were heat treated between 775∘C and 825∘C for 30 and 60 min in oxygen atmosphere and characterized by X-ray diffraction (XRD), impedance as well as Mössbauer spectroscopy. The cubic phase of Bi0.4Sr0.6FeO3 was successfully obtained in samples milled for only 2 h and a subsequent calcination at 800∘C. Irrespective of milling time, heat treatments at lower temperatures (775∘C) still show spurious phases such as Sr0.23Bi0.76O1.1 (30 min) and Sr0.53Bi1.72O3 (60 min). Impedance spectroscopy show high values (105–109) Ω indicating strong structural bond between the atoms of the system and activation energies for the strontium ion around 04 eV. These results show a single dynamic behavior in a range from 1 to 2*105 Hz enabling data adjustment and analysis to a RC circuit. Conductivity results normally show a behavior that obeys the universal law of Jonscher’s relaxation (σ = σ Dc + α ω n) with values for the exponent n (0.8 < n < 1) typical in these structures. Mössbauer spectrometry measurements reveal that the hyperfine magnetic field of the precursors and milled powders corresponds to hematite 512 T. After the thermal treatment of the samples, the mean hyperfine field decreases to 489 ± 0.5 T showing the Bi and Sr atoms diffusion, (non- magnetic) in Fe2O3. While the result of isomer shift corresponds to a Fe+3 oxidation state irrespective of the heat treatment